How Far Takaful Efficiency Has Been Researched? : A Bibliometric Approach from Dimensions Database - Mia Sari; Siti Maysyaroh (SMART Insight, 2022)
This study utilizes a bibliometric approach to investigate efficiency in the takaful industry, which has been under-researched in the literature. Focusing on the theme of